Review: Agricultural Wastes as a Source of Silica Material - Novie Permatasari; Transmissia Noviska Sucahya; Asep Bayu Dani Nandiyanto (Indonesian Journal of Science and Technology, 2016)
Silica is the most abundant components in the earth's crust and is made by way of synthesis for use in the application of technology. Silica are generally found commercially as alkoxysilane compounds (i.e such as tetraethylorthosilicate (TEOS), sodium silicate, and tetramethylorthosilicat). However, these compounds can have a negative impact on health. Thus, further approaches to find the source of silica that is safer, cheaper, and more environmentally friendly is inevitable. However, not all summary journals are thoroughly discussed the silica sources. Further, method of isolation and application of the silica from agricultural waste is limited. This paper reported studied several sources of silica derived from agricultural waste, such as rice husk, rice straw, corn cobs, and bagasse. In addition, this paper discussed also about the method of isolation of silica from agricultural waste, and its application as a catalyst.